A genotypic trade‐off between constitutive resistance to viral infection and host growth rate. (21st October 2018) - Bartlett, Lewis J.; Wilfert, Lena; Boots, Michael
Abstract: Genotypic trade‐offs are fundamental to the understanding of the evolution of life‐history traits. In particular, the evolution of optimal host defense and the maintenance of variation in defense against infectious disease is thought to be underpinned by such evolutionary trade‐offs. However, empirical demonstrations of these trade‐offs that satisfy the strict assumptions made by theoretical models are rare. Additionally, none of these trade‐offs have yet been shown to be robustly replicable using a variety of different experimental approaches to rule out confounding issues with particular experimental designs. Here, we use inbred isolines as a novel experimental approach to test whether a trade‐off between viral resistance and growth rate in Plodia interpunctella, previously demonstrated by multiple selection experiments, is robust and meets the strict criteria required to underpin theoretical work in this field. Critically, we demonstrate that this trade‐off is both genetic and constitutive. This finding helps support the large body of theory that relies on these assumptions, and makes this trade‐off for resistance unique in being replicated through multiple experimental approaches and definitively shown to be genetic and constitutive.